EVALUATION BY EACH ODOR AND PROGNOSIS IN PATIENTS WITH POST-VIRAL OLFACTORY DYSFUNCTION - Mori, Eri; Otori, Nobuyoshi; Mitsuyama, Chieko; Kurashima, Ayako; Nagai, Monami; Tei, Masayoshi; Kojima, Hiromi; Sugita, Yuiko; Sekine, Rumi (JIBI INKOKA TEMBO, 2018)
Post-viral olfactory dysfunction (PVOD) is an olfactory disorder caused by upper respiratory tract infection, whose pathophysiology has not yet been clearly elucidated. In clinical practice, we often encounter differences in the results and degree of recovery depending on the odor during assessments made with a T&T olfactometer or Open Essence. Investigating the severity of the disorder and degree of recovery for different odors may contribute to elucidation of the pathophysiology of the disorder. However, the degree of olfactory impairment and effect of therapy are evaluated based on the average cognitive value for odors, and the results for each odor are not reflected. In this study, we investigated the changes in the results for each odor using both the tests and attempted to identify factors affecting the prognosis.　The subjects were 109 patients visiting the Otorhinolaryngology outpatient clinic at the hospital of Tokyo Jikei Medical University from May 2009 to March 2015, who were diagnosed as having PVOD. The efficacy of therapy was evaluated at the first visit, at 3 months from the first visit, and at 9 months after the first visit. The improvement rate was 58.3%. Assessment with the T&T olfactometer revealed significant improvement in the results for all odors during the course of treatment. The factors affecting the prognosis were the disease duration and the detection threshold value for odor E at the first visit.　The possibility has been suggested that degree of disability and recovery may differ depends on the odor. And we should pay attention to difference of odor in evaluation of disorder and treatment.